2024
DOI: 10.3390/nu16030357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermittent Fasting on Cardiometabolic Health in the Chinese Population: A Meta-Analysis of Randomized Controlled Trials

Katy Cheung,
Vicky Chan,
Stephanie Chan
et al.

Abstract: The efficacy of intermittent fasting (IF), as an emerging weight management strategy, in improving cardiometabolic health has been evaluated in various populations, but that among Chinese individuals has not been systematically studied. A comprehensive search on multiple databases was performed to identify eligible randomized controlled trials (RCTs) up to October 2022. The primary outcome was post-intervention weight loss, and secondary outcomes included changes in cardiometabolic indicators. Effect estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…No serious adverse effects were reported globally. In conclusion, the studies confirmed that IF could be useful in reducing weight, whereas IF could not be helpful in improving some cardiometabolic parameters, including blood pressure [59]. This contrasted with a previous metaanalysis (694 individuals from different countries), in which a similar trend was observed, but the authors indicated a significant reduction in systolic blood pressure (-4.15 mmHg) [60], while longer IF interventions were found to positively modify the pressure outcome with statistically significant results (one-year observational study, 1422 individuals; -10.9 mmHg for systolic pressure and -5.8 mmHg for diastolic pressure) [61].…”
Section: A General View Of If Approachesmentioning
confidence: 73%
See 1 more Smart Citation
“…No serious adverse effects were reported globally. In conclusion, the studies confirmed that IF could be useful in reducing weight, whereas IF could not be helpful in improving some cardiometabolic parameters, including blood pressure [59]. This contrasted with a previous metaanalysis (694 individuals from different countries), in which a similar trend was observed, but the authors indicated a significant reduction in systolic blood pressure (-4.15 mmHg) [60], while longer IF interventions were found to positively modify the pressure outcome with statistically significant results (one-year observational study, 1422 individuals; -10.9 mmHg for systolic pressure and -5.8 mmHg for diastolic pressure) [61].…”
Section: A General View Of If Approachesmentioning
confidence: 73%
“…In addition, considering the specific population, the results did not differ from those previously presented. In fact, a recent meta-analysis, using a random-effects model, conducted by Cheung and collaborators in which the Chinese population was considered demonstrated heterogeneity on the considered outcomes [59]. In particular, based on the proposed inclusion criteria, the authors considered nine random-ized clinical trials for a total of 899 individuals, and the IF dietary regimen applied for at least 3 weeks in the intervention groups (different types of interventions) was compared with controls (ad libitum diet and CR).…”
Section: A General View Of If Approachesmentioning
confidence: 99%
“…No serious adverse effects were reported globally. In conclusion, the studies confirmed that IF could be useful in reducing weight, whereas IF could not be helpful in improving some cardiometabolic parameters, including blood pressure [66]. This contrasted with a previous meta-analysis (694 individuals from different countries), in which a similar trend was observed, but the authors indicated a significant reduction in systolic blood pressure (−4.15 mmHg) [67], while longer IF interventions were found to positively modify the pressure outcome with statistically significant results (one-year observational study, 1422 individuals; −10.9 mmHg for systolic pressure and −5.8 mmHg for diastolic pressure).…”
Section: A General View Of If Approachesmentioning
confidence: 73%
“…In addition, considering the specific population, the results did not differ from those previously presented. In fact, a recent meta-analysis using a random-effects model, conducted by Cheung and collaborators, in which the Chinese population was considered, demonstrated heterogeneity n the considered outcomes [66]. In particular, based on the proposed inclusion criteria, the authors considered nine randomized controlled trials with a total of 899 individuals, and the IF dietary regimen applied for at least 3 weeks in the intervention groups (different types of interventions) was compared with controls (ad libitum diet and CR).…”
Section: A General View Of If Approachesmentioning
confidence: 99%